La nouvelle fantastique au XXe siècle: le charme trouble du mystère et du non-dit - Gadomska, Katarzyna (Romanica Silesiana)
Katarzyna Gadomska devotes her text to the science-fiction literature, predestined to create the aura of understatement by nature. The author focuses on the short stories by Bours and Andrevon. Keywords: Bours; Andrevon; mystery tale; the unsaid; secrets